Identifying Zambia's industrial fortification options: Toward overcoming the food and nutrition information gap-induced impasse - Fiedler, John L.; Lividini, Keith; Zulu, Rodah; Kabaghe, Gladys; Tehinse, John; Bermudez, Odilia I. (SAGE Publications, 2013)
Zambia was a pioneer when it started fortifying sugar with vitamin A in 1998. Micronutrient deficiencies—especially among young children—have changed little over the past decade. In 2008 an initiative to introduce fortified flours was halted when last-hour questions about the program could not be answered.To provide information about the need, coverage, and impact of alternative fortification portfolio options to help Zambia overcome its fortification impasse.Using household data from the 2006 Living Conditions Monitoring Survey, apparent micronutrient intake levels and apparent consumption levels of sugar, vegetable oil, wheat flour and maize meal were estimated. The household level data were used to estimate individual intakes by assuming that food was distributed among household members in direct proportion to their share of the household's total adult consumption equivalent. Intake adequacy was measured relative to age- and gender-specific Estimated Average Requirements. Combining information on the industrial structure and estimated fortifiable quantities consumed of each food, and assuming the nutrient content is that specified in official regulations, simulations were conducted of the coverage and impact of 14 fortification portfolios.Maize, the most commonly consumed food, is consumed in a fortifiable form by only 23% of the population. Sugar fortification is estimated to have reduced inadequate intake of vitamin A from 87% to 79%. Introducing oil fortification could reduce the prevalence of inadequate vitamin A intake to 61%, and fortifying roller and breakfast maize meal would further reduce it to 57%, and reduce inadequate iron and zinc intakes by 2.2% and 5.5%, respectively. Implementing WHO flour guidelines would triple the potential iron and zinc impacts.Analysis of LCMS apparent consumption data have helped address important information gaps and provide better understanding of the coverage and impacts of alternative fortification portfolios.